Respuesta :

suspho

Answer:

Step-by-step explanation:

b²-5b-5=

we substitute the values

remember pemdas

6²-5*6-5=

36-30-5=

1

------------------------

Answer:

The answer is 1.

Step-by-step explanation:

Question :

Evaluate the expression when b = 6

b²– 5b – 5

Solution :

To solve this question we'll substitute the values of b in this given expression :

[tex] \implies{\tt{{b}^{2} - 5b - 5}}[/tex]

[tex] \implies{\tt{{(6)}^{2} - 5 \times 6 - 5}}[/tex]

[tex] \implies{\tt{{(6 \times 6)}- 30 - 5}}[/tex]

[tex] \implies{\tt{36- 30 - 5}}[/tex]

[tex] \implies{\tt{36- 35}}[/tex]

[tex] \implies{\tt{1}}[/tex]

Hence, the answer is 1.

[tex]\rule{300}{2.5}[/tex]

ACCESS MORE